Assessment Of Nonlinear Static (Pushover) Procedures For Seismic Evaluation Of Reinforced Concrete Structures - Taghavipour, Saber (2013)
In general, earthquake is one of the most serious natural disasters that mankind has ever suffered since the first day of civilization. Hence, the seismic performance of structures subjected to earthquake always becomes critical issues. This thesis presents the assessment of current nonlinear static procedures using nonlinear time history procedure. The selected pushover procedures in this research are consisting of Coefficient Method, Capacity Spectrum Method and Modal Pushover Method. Since plastic hinge length is an effective parameter in pushover analysis, this study discusses different plastic hinge lengths. These lengths are calculated for both default and user-defined cases. In this context, 2, 5, 8 and 12 storey frame were selected to represent the real low, medium and high rise regular reinforcement concrete structure. The results of the pushover analysis indicated that behaviour of the structures using modal pushover analysis method and coefficient method (under certain conditions) were more realistically than those analysed using capacity spectrum method. Moreover, the comparison of the results obtained from selected plastic hinge length reveals that, although the results of user-defined and default plastic hinge length in yielding state are almost similar, the results in ultimate state are significantly different. Therefore, it can be concluded that in this study proposed user-defined plastic hinge length shows better performance of hinge in analysis as compared to default plastic hinge length.